The Effect of Local and Systemic Factors on Dental Implant Failure – Analysis of 670 Patients with 1260 Implants - Željko Rotim; Ivica Pelivan; Ivan Sabol; Mato Sušić; Amir Ćatić; Andrija Petar Bošnjak (Acta Clinica Croatica, 2021)
The etiopathogenesis of dental implant failure is multifactorial and may include numerous local and systemic factors, however, studies including both local and systemic factors are still lacking. Therefore, the aim of this study was to evaluate whether periodontal disease, oral hygiene index, i.e. bleeding on probing (BOP), full mouth plaque index (FMPI), smoking, systemic diseases, as well as implant characteristics (length and diameter) affect failure of implant-prosthodontic therapy. Data on 670 patients were retrieved in whom 1260 dental implants had been placed and followedup for at least five to ten years. Categorical data were analyzed by the χ2-test, whereas Mann-Whitney test was used for continuous variables (age, BOP and FMPI). The values of p<0.05 were considered significant. The effect of local and systemic factors on the success of implant-prosthodontic therapy was assessed by multiple logistic regression analysis. Forty-five (6.7%) patients had systemic diseases, of which diabetes mellitus was most common, followed by atherosclerosis, diabetes and atherosclerosis, diabetes mellitus type 1, lymphoma, and hepatitis C. One-third (33.4%) of the patients were smokers. Periodontal disease was present in 170 patients, while 500 patients were without periodontal disease. Nine implants were lost during the period of five years. There were no differences regarding the type of implant or type of connection to the prosthetic suprastructure. However, most of these patients had a periodontal disease. There were no significant differences in dental implant failure rates between smokers and non-smokers or between patients with and without systemic diseases. Furthermore, the results of this study showed that implant type (straight vs. tapered) and type of connection with prosthodontic appliance (cemented or screw retained) did not affect BOP and FMPI. In smokers, significant improvement of BOP and FMPI was noticed. Initially, smokers had a significantly worse BOP (0.0037) when compared to non-smokers; however, there were no differences regarding FMPI (p=0.4218) between the two groups. In patients with periodontal disease, improvement of BOP and FMPI was seen at 5-year follow-up and no significant differences were found when compared to patients without periodontal disease. There were no significant differences in BOP and FMPI between patients with and without diabetes at 5-year follow-up. Atherosclerosis had a significant negative effect on BOP, but not on FMPI at 5-year follow-up. It is concluded that periodontal disease had a significant impact on the implant-prosthodontic therapy.